CNS demyelinating events in primary Sjögren's syndrome: A single-center case series on the clinical phenotype - Afzali, Ali M.; Moog, Philipp; Kalluri, Sudhakar Reddy; Hofauer, Benedikt; Knopf, Andreas; Kirschke, Jan Stefan; Hemmer, Bernhard; Berthele, Achim (Frontiers in Neurology, 2023)
Objective The study aimed to assess the prevalence, clinical characteristics, and therapeutic outcomes of the central nervous system (CNS) demyelinating disease in a large cohort of primary Sjögren's syndrome (pSS). Methods This is an explorative cross-sectional study of patients with pSS seen in the departments of rheumatology, otorhinolaryngology, or neurology of a tertiary university center between January 2015 and September 2021. Results In a cohort of 194 pSS patients, 22 patients had a CNS manifestation. In this CNS group, 19 patients had a lesion pattern suggestive of demyelination. While there were no obvious differences in the patients' epidemiological disposition or rate of other extraglandular manifestations, the CNS group differed from the remaining patients with pSS by having less glandular manifestations but a higher seroprevalence for anti-SSA/Ro antibodies. Notably, patients with CNS manifestations were often diagnosed with multiple sclerosis (MS) and treated as such, although age and disease course were atypical of MS. Many first-line MS agents were ineffective in these “MS look-alikes”; however, the disease course was benign with B-cell-depleting agents. Conclusion Neurological symptoms of pSS are common and clinically manifest mainly as myelitis or optic neuritis. Notably, in the CNS, the pSS phenotype can overlap with MS. The prevailing disease is crucial since it has a major impact on the long-term clinical outcome and the choice of disease-modifying agents. Although our observations neither confirm pSS as a more appropriate diagnosis nor rule out simple comorbidity, physicians should consider pSS in the extended diagnostic workup of CNS autoimmune diseases.